2001
DOI: 10.1093/jn/131.11.2928
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to High Levels of Dietary Iron Fortification Increases Lipid Peroxidation in the Mucosa of the Rat Large Intestine

Abstract: There is increasing evidence that excess dietary iron may be a risk factor for colorectal cancer. However, the majority of animal studies looking at possible mechanism have used unrealistically high concentrations of iron. The current study was designed to test whether chronic exposure to high levels of iron fortification affects the free radical generating capacity of the lumenal contents, mucosal lipid peroxidation and crypt cell proliferation. Rats were fed diets containing either 29 mg/kg or 102 mg/kg of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 29 publications
1
43
0
6
Order By: Relevance
“…It has been suggested that chronic iron intake can affect intestinal homeostasis by altering intestinal microbial composition, oxidative stress, inflammation, etc. [13,15,16,[17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that chronic iron intake can affect intestinal homeostasis by altering intestinal microbial composition, oxidative stress, inflammation, etc. [13,15,16,[17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…Red meat components hypothesized to be contributory factors to colon cancer etiology include DNA-reactive heterocyclic amines formed during cooking [23,29]; animal fat, which may act by increasing intracolonic concentrations of membrane-damaging bile acids and fatty acids [30][31][32][33]; and, iron content of red meat [34][35][36][37][38]. Most dietary iron is not absorbed but is concentrated in the feces at levels that may be up to 10-fold higher than that found in tissues [39].…”
Section: Risk Factors For Crcmentioning
confidence: 99%
“…Therefore, it was assumed that orally taken iron which fails to be absorbed and reaches the colon may damage mucosa by intensifying formation of free radicals to a critical level (71,76). Impact of prolonged intake of iron on mucosal lipid peroxidation and production of free radicals in the colon and cecum was analyzed in male Wistar rats by Lund and others and demonstrated to be able to elevate the both measured variables in large intestine and cecum (77).…”
Section: Colorectal Cancermentioning
confidence: 99%